Radiographic examination and dental treatment of patients with florid cemento-bone dysplasia: Narrative review - de Carvalho, Daniel Coelho; de Sousa, Joana Albuquerque Bastos; Corrêa, Mirtes Maria Ferreira; Lima, Caio de Góes Pezzino; do Nascimento Neto, Isidório Alexandre; Barros, Vitor Vinicius Costa; Nascimento, Alessandra Fialho; Sousa, Francenilde Silva de (Seven Editora, 2023)
Flowering cemento-osseous dysplasia is a benign condition characterized by changes in the process of bone formation and the deposit of mineralized tissue in the soft tissues of the oral cavity. The diagnosis of flowering cemento-osseous dysplasia is accompanied by radiographic examinations, and treatment depends on the severity of the condition and the patient’s symptoms. Thus, it is important for patients to undergo periodic dental examinations to monitor the progression of the condition. A literature review on the radiographic examination and dental treatment of patients with this condition was conducted with searches in February 2023, in the PubMed, Scielo, Lilacs and BBO databases, following certain criteria for selection. Seven articles were identified and in them, there is evidence that some patients may not have clinical symptoms, but it is possible that patients develop periodontal disease. Having, as a potential complication of the condition, the possibility of losing teeth due to the rapid progression of periodontal disease. In addition, in rare cases, flowering cemento-osseous dysplasia can progress to a more serious condition such as a cemento-ossifying fibro-osseous lesion or an adenomatous odontogenic tumor. DOI:https://doi.org/10.56238/globalhealthprespesc-060